The case management workbook : defining the role of physicians, nurses and case managers - Murer, Cherilyn G.; Brick, Lyndean Lenhoff; Murer, Michael A. (Productivity Press, an imprint of Taylor and Francis, 2011)
Case management has become one of the most effective means by which a continuum of care functions effectively and efficiently. A complete examination of the application of continuum of care, The Case Management Workbook: Defining the Role of Physicians, Nurses, and Case Managers defines the roles of the case management team and provides an overview of key post acute venues of care. It supplies an overview of the process, its structure, and the responsibility of each member of the team. The book discusses how managing the care of the patient in today's healthcare environment will take a concerted effort from the entire case management team?not just a handful of case managers.